Development of a Cell-Based Functional Assay for the Detection of Clostridium botulinum Neurotoxin Types A and E - Uma Basavanna; Tim Muruvanda; Eric W. Brown; Shashi K. Sharma (International Journal of Microbiology)
The standard procedure for definitive detection of BoNT-producing Clostridia is a culture method combined with neurotoxin detection using a standard mouse bioassay (MBA). The mouse bioassay is highly sensitive and specific, but it is expensive and time-consuming, and there are ethical concerns due to use of laboratory animals. Cell-based assays provide an alternative to the MBA in screening for BoNT-producing Clostridia. Here, we describe a cell-based assay utilizing a fluorescence reporter construct expressed in a neuronal cell model to study toxin activity in situ. Our data indicates that the assay can detect as little as 100 pM BoNT/A activity within living cells, and the assay is currently being evaluated for the analysis of BoNT in food matrices. Among available in vitro assays, we believe that cell-based assays are widely applicable in high-throughput screenings and have the potential to at least reduce and refine animal assays if not replace it.